2012
DOI: 10.1088/0957-0233/23/3/035001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dimensional stability of a line scale made of low thermal expansion ceramic NEXCERA

Abstract: Length measurement was carried out on line scales made of the ultralow-expansion ceramic NEXCERA™ and synthetic quartz for 13 months. 550 mm long precision line scales made of the two materials were manufactured and their changes in length were measured over the same period, using a high-precision laser-interferometric line scale calibration system. NEXCERA was used to evaluate its long-term dimensional stability. Synthetic quartz was used because of its long-term stability to ensure the stability of the long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
1
12
1
Order By: Relevance
“…NEXCERA has a high specific stiffness, extremely low coefficient of thermal expansion (CTE) and excellent long term stability. In the previous paper, the long term dimensional stability of NEXCERA was reported as 0.01 ± 0.01 ppm over 13 months [1]. The excellent polishing characteristics and new development of material composition suitable for mirror applications were also reported in a recent paper.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…NEXCERA has a high specific stiffness, extremely low coefficient of thermal expansion (CTE) and excellent long term stability. In the previous paper, the long term dimensional stability of NEXCERA was reported as 0.01 ± 0.01 ppm over 13 months [1]. The excellent polishing characteristics and new development of material composition suitable for mirror applications were also reported in a recent paper.…”
Section: Introductionmentioning
confidence: 84%
“…NEXCERA MATERIAL PROPERTIES Ultra low thermal expansion ceramic NEXCERA is a cordierite (2MgO-2Al 2 O 3 -5SiO 2 ) based ceramic and has advanced material properties to meet severe requirements of space applications. Its key properties are a high specific stiffness (140 GPa / 2.55 g/cm 3 ) [2] and high long term stability (0.01 ppm / 13 months) [1] combined with an extremely low CTE (< 0.03 ppm/K) at room temperature [2]. Its high stability against thermal disturbance and secular change allow it to be applied to optical components in earth orbiting satellites.…”
Section: Introductionmentioning
confidence: 99%
“…The error of our NEXCERA drift rate measurement is approximately 0.01 × 10 −8 yr −1 , 50 times lower compared to the measurement in ref. [14]. To ensure that the long-term frequency drift measurement was not affected by the quality of the optical contacts, we tested them visually and mechanically after completion of the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The first characterization of the dimensional stability of NEXCERA was recently reported by Takahashi [14]. Length measurements of line scales made from NEXCERA showed that the ceramic has good long-term dimensional stability.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-low-expansion glass (ULE) is today the most common material for use at or near room temperature. Another promising material is the ceramic Nexcera [12][13][14] . However, the Brownian motion imposes a fundamental limitation to their length stability 15 .…”
Section: Introductionmentioning
confidence: 99%